2019
DOI: 10.1177/0194599818825461
|View full text |Cite
|
Sign up to set email alerts
|

Children with Cleft Palate: Predictors of Otologic Issues in the First 10 Years

Abstract: Objective To evaluate the characteristics of children with cleft palate associated with persistent otologic issues in the first 10 years of life. Study Design Case series with chart review. Setting Single academic center. Subjects and Methods Children born with cleft palate from 2003 to 2007 and treated by the UC Davis Cleft and Craniofacial Team between January 2003 and December 2017 were included in the study. Data from 143 patients were analyzed via Wilcoxon rank sum and Fisher exact tests for univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Although the exact age is not known, children with cleft palate are thought to have a median age of normalized Eustachian tube function well past the population average of 7 years . With regard to predictive clinical characteristics, previous work from our group would also suggest that need for revision cleft palate repair or speech surgery may be associated with longer time to normal Eustachian tube function, but that severity of palatal clefting is not a factor …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the exact age is not known, children with cleft palate are thought to have a median age of normalized Eustachian tube function well past the population average of 7 years . With regard to predictive clinical characteristics, previous work from our group would also suggest that need for revision cleft palate repair or speech surgery may be associated with longer time to normal Eustachian tube function, but that severity of palatal clefting is not a factor …”
Section: Introductionmentioning
confidence: 95%
“…3 With regard to predictive clinical characteristics, previous work from our group would also suggest that need for revision cleft palate repair or speech surgery may be associated with longer time to normal Eustachian tube function, but that severity of palatal clefting is not a factor. 16 The purpose of this study is to expand on our prior investigation of otologic outcomes in children with cleft palate by characterizing the duration of Eustachian tube dysfunction with a longitudinal analysis of tympanometric data. Rather than focusing on otologic outcomes (e.g., tympanic membrane perforation) at 10 years of age as in our previous study, 16 all tympanometric results for children with cleft palate (and those with cleft lip but not cleft palate as a reference group) born in the years 2003 through 2007 and followed at our center were evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CP (Funamura et al, 2019a) and SMCP (Kwinter et al, 2018) are at higher risk for Eustachian tube dysfunction (ETD) than the general population. A recent study indicated that, among patients with CP, history of revision palatoplasty or speech surgery was a risk factor for ETD (Funamura et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic otitis media with effusion, conductive hearing loss, TM perforation, cholesteatoma, and TM retraction are all common in children with CLP (Funamura et al, 2019). These children often require multiple surgical procedures in their first few years of life.…”
Section: Introductionmentioning
confidence: 99%